Systematic review and meta-analysis of the interventional effects of resveratrol in a rat model of myocardial ischemia-reperfusion injury - Zhang, Dong-Ze; Jia, Ming-Yang; Wei, Hong-Yu; Yao, Ming; Jiang, Li-Hong (Frontiers in Pharmacology, 2024)
Objective: To evaluate the intervention effect of resveratrol on rat model of myocardial ischemiareperfusion injury.The relevant studies on the intervention of resveratrol on rat models of myocardial ischemia reperfusion injury were searched in PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang and China Science and Technology Journal Database from the start of database establishment to January 2023. Data were extracted from studies that met the inclusion criteria. The results included electrocardiogram (ECG) and myocardial injury markers: ST changes, cardiac troponin I (cTn-I), cardiac troponin T (cTn-T), creatine kinase (CK), creatine kinase-MB (CK-MB) and lactate dehydrogenase (LDH); hemodynamic indicators: heart rate (HR), left ventricular diastolic pressure (LVDP), left ventricular end-diastolic pressure (LVEDP), left ventricular systolic pressure (LVSP), maximum rate of increase of left ventricular pressure (+dp/dtmax), maximum rate of decrease of left ventricular pressure (-dp/dtmax); oxidative damage indicators: nitric oxide (NO), reactive oxygen species (ROS), superoxide dismutase (SOD), malondialdehyde (MDA); inflammatory factors: tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6); apoptosis index: B-cell lymphoma-2 (Bcl-2), BCL2-Associated X (Bax), cardiomyocyte apoptosis index (AI); heart tissue structure: myocardial infarction size. Finally, a meta-analysis of these results was conducted. The methodological quality of the studies was assessed using the SYRCLE Bias Risk tool.Results: A total of 43 studies were included in the meta-analysis, and the quality of the included studies was assessed. It was found that the evidence quality of these 43 studies was low, and no study was judged to have low risk bias in all risk assessments. The results showed that resveratrol could reduce ST segment, cTn-I, cTn-T, CK, CK-MB, LDH, LVEDP, ROS, MDA, TNF-α, IL-6, AI levels and myocardial infarction size. HR, LVDP, LVSP, +dp/dtmax, NO, Bcl-2, and SOD levels were increased. However, resveratrol had no significant effect on -dp/dtmax and Bax outcome measures.Resveratrol can reduce ST segment in rat model of myocardial ischemia-reperfusion injury, alleviate myocardial injury, improve ventricular systolic and diastolic ability in hemodynamics, reduce inflammatory response and oxidative damage, and reduce myocardial necrosis and apoptosis. Due to the low quality of the methodologies included in the studies, additional research is required.